2018
DOI: 10.1371/journal.pone.0207581
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primary solitary fibrous tumors involving the pelvic ring

Abstract: The surgical treatment of primary solitary fibrous tumors (SFT) involving the pelvic ring has not been reported previously. In this study, we aimed to evaluate the efficacy of surgical treatment for this disease. From 2009 to 2015, 13 patients underwent tumor resection at our hospital, with an average age of 49.5 years (27–68 years). Four patients underwent en bloc resection, and 9 patients underwent piecemeal resections. A Chi-square test was used to compare the postoperative recurrence rates between the en b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Although SFTs were initially reported only in the visceral pleura, these tumors can occur in almost every part of the human body [ 2 ]. However, a perineal location is rare, and to our knowledge, our case is the 4 th reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SFTs were initially reported only in the visceral pleura, these tumors can occur in almost every part of the human body [ 2 ]. However, a perineal location is rare, and to our knowledge, our case is the 4 th reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Klemperer and Rabin first reported them in 1931 [ 1 ]; however, over the years, SFTs have been found in other extrapleural sites. SFTs have been found in the limbs, pelvic cavity, abdominal cavity, neck, and central nervous system [ 2 , 3 ]. A perianal location is rare for this type of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported on cases of SFT located in the pelvic region (21,22). However, to the best of our knowledge, SFTs spanning the obturator fossa with involvement of obturator nerve have not been reported to date.…”
Section: Discussionmentioning
confidence: 91%
“…Our center is the largest sacral tumor treatment center in the country and has accumulated rich experience in sacral tumor resection. Although total en bloc sacrectomy is traditionally performed in stages using combined anterior and posterior approaches, we have explored and reported one‐stage total en bloc sacrectomy via a single posterior approach to reduce operative time, blood loss, and surgical complications …”
Section: Introductionmentioning
confidence: 99%
“…and reported one-stage total en bloc sacrectomy via a single posterior approach to reduce operative time, blood loss, and surgical complications. [4][5][6][7][10][11][12] However, total en bloc sacrectomy can impair bladder and bowel function, sexual function, and lower limb function due to nerve sacrifice (S1 and below) during surgery, thereby seriously affecting ambulation and daily living and presenting challenges for maintenance of healthy psychological and social functioning. Therefore, this patient population substantially differs from those with nonsacral bone tumors and those undergoing lower sacral tumor resection.…”
mentioning
confidence: 99%